Collaborative Governance in Village-Owned Enterprises: A Case Study of Traditional Rice Field-Based BUMDes in Tubo Selatan - Anwar, Mawardi; Nurkidam, A; Mahyuddin, Mahyuddin; Bakri, Muhiddin (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2025)
Badan Usaha Milik Desa (BUMDes) or Village -Owned Enterprises have emerged as a strategic policy instrument for empowering rural communities through participatory economic management. This study examined collaborative arrangements between the village government and community members in managing traditional rice fields (sawah adat) under the BUMDes framework in Tubo Selatan Village, and explored how these arrangements fostered social solidarity. Historically, sawah adat functioned as a non-monetary compensation mechanism for village officials; however, it has evolved into a collective economic initiative that redistributes benefits and strengthens community welfare. By using a qualitative case study design , the research investigates interaction patterns, collaborat ive roles, and solidarity values embedded in the sawah adat –based BUMDes model. Twelve informants were selected purposively from government actors, BUMDes administrators, and farming communities. Data were gathered through observation, semi-structured interviews, and document analysis, and were examined using a structured process of data reduction, data display, and conclusion drawing within the framework of collaborative governance theory. Findings indicate that collaboration is institutionalized through transparent registration mechanisms, shared decision -making, and a proportional distribution of harvest yields between farmers and the BUMDes. The governance model ensures fair benefit - sharing, reinforces mutual responsibility, and sustains the cultural value of gotong royong. Moreover, deliberative processes grounded in accountability enhance trust, reduce conflict, and facilitate sustained cooperation. The management of traditional rice fields therefore functions not only as an economic driver but also as a catalyst for strengthening collective identity and social cohesion within the rural community.